Das Russisch-Deutsche Woerterbuch von Iwan Pawlowsky Eine metalexikographische Analyse - Böhler, Claudia (Slavistische Beitraege, 2003)
The Russian-German dictionary by Pawlowsky, which first appeared in Riga in 1859, is a little-noticed in Slavic jewel so far. This is astonishing precisely because it is an indispensable tool in reading the Russian classics, its bilingualism is authentic and quite reliable down to scientific nomenclature and also not only records but also explains a great deal of idiomatic and probiotic. The aim of this work is to contribute to the history of Russian-German lexicography through a metalexographic single analysis of this work. The centuries-old disinterest in the results of lexicographical work also explains that Ivan Pawlowsky's Russian-German dictionary, to this day, must be considered terra incognita. Secondary: Pavlovsky's Russian-German dictionary.